Properties of Interlocking Block Containing Fly Ash and Bottom Ash - CHAIMOON, KRIT (Srinakharinwirot University Engineering Journal, 2019)
This research studied the use of fly ash and bottom ash in manufacturing of load-bearing interlocking block by replacing cement and laterite soil, respectively, at 0, 5, 10, 15, 20 and 25% by weight. This study used mixing ratio of cement to laterite soil of 1:7 by weight. The basic properties including compressive strengths (at 14, 28 and 90 days), water absorption (at 28 days), and unit weight (at 28 days) of the interlocking blocks were tested and determined. From the test results, it was found that interlocking blocks mixed with fly ash and bottom ash in appropriate proportions had the required properties complying with the Thai Community Product Standard for interlocking block.